Prognostic impact of multiple fragmented QRS on cardiac events in idiopathic dilated cardiomyopathy. Issue 2 (19th November 2020) - Marume, Kyohei; Noguchi, Teruo; Kamakura, Tsukasa; Tateishi, Emi; Morita, Yoshiaki; Miura, Hiroyuki; Nakaoku, Yuriko; Nishimura, Kunihiro; Yamada, Naoaki; Tsujita, Kenichi; Izumi, Chisato; Kusano, Kengo; et al.
Abstract: Aims : To evaluate the prognostic impact of fragmented QRS (fQRS) on idiopathic dilated cardiomyopathy (DCM). Methods and results : We conducted a prospective observational study of 290 consecutive patients with DCM (left ventricular ejection fraction ≤ 40%) and narrow QRS who underwent cardiac magnetic resonance. We defined fQRS as the presence of various RSR′ patterns in ≥2 contiguous leads representing the anterior (V1–V5), inferior (II, III, and aVF), or lateral (I, aVL, and V6) myocardial segments. Multiple fQRS was defined as the presence of fQRS in ≥2 myocardial segments. Patients were divided into three groups: no fQRS, single fQRS, or multiple fQRS. The primary endpoint was a composite of hard cardiac events consisting of heart failure death, sudden cardiac death (SCD), or aborted SCD. The secondary endpoints were all-cause death and arrhythmic event. During a median follow-up of 3.8 years (interquartile range, 1.8–6.2), 31 (11%) patients experienced hard cardiac events. Kaplan–Meier analysis showed that the rates of hard cardiac events and all-cause death were similar in the single-fQRS and no-fQRS groups and higher in the multiple-fQRS group ( P = 0.004 and P = 0.017, respectively). Multivariable Cox regression identified that multiple fQRS is a significant predictor of hard cardiac events (hazard ratio, 2.23; 95% confidence interval, 1.07–4.62; P = 0.032). The multiple-fQRS group had the highest prevalence of a diffuse late gadolinium enhancement pattern (no fQRS, 21%; single fQRS, 22%; multiple fQRS, 39%; P < 0.001). Conclusion : Multiple fQRS, but not single fQRS, is associated with future hard cardiac events in patients with DCM. Graphical Abstract: